MINAT SISWA PUTERI TERHADAP MATA PELAJARAN PENJASORKES DI SD TANJUNG BERINGIN MUSI RAWAS UTARA - Niku Saputra; Wawan Syafutra; Suparman (LP3MKIL, 2024)
Tanjung iBeringin iElementary iSchool iin iMusi iRawas iUtara iis ione iof ithe ischools ithat iconduct iPhysical iEducation i(Penjasorkes) ilearning. iHowever, iin iits iimplementation, ithere iare istudents iwho iare iless ienthusiastic, iespecially ifemale istudents. iThis icondition iis iinfluenced iby ivarious ifactors, iincluding ithe ilack iof imotivation iamong ifemale istudents, ithe ieducational ibackground iof iPenjasorkes iteachers, ithe imodifications iin ithe iteaching iapproach, ithe iavailable ifacilities iand iinfrastructure, isupport ifrom ithe ischool iprincipal, ias iwell ias ithe icurriculum iand iteaching iplanning. iThis iresearch iis ia idescriptive istudy iaimed iat idepicting ithe imotivation iof ifemale istudents itowards iPenjasorkes ilearning iat iTanjung iBeringin iElementary iSchool iin iMusi iRawas iUtara. iThe iresearch iwas iconducted iin iJuly i2023 iwith ia ipopulation iof i27 istudents. iThe isample iwas itaken iusing ithe itotal isampling itechnique, iso ithe ientire ipopulation ibecame ithe iresearch isample. iThe idata icollection iinstrument iused iwas ia iquestionnaire ior isurvey iwith ithe iGuttman iscale. iData iwere ianalyzed iusing ifrequency idistribution iin ipercentage iform. iThe iresearch iresults ishowed ithat ithe istudents' iinterest ilevel ireached i80.74%, iindicating ithat ithe imotivation iof ifemale istudents itowards ithe imodification iof iPenjasorkes ilearning iat iTanjung iBeringin iElementary iSchool iin iMusi iRawas iUtara iis iin ithe igood icategory. iThe ilevel iof imodification iachievement iin iPenjasorkes ilearning ireached i78.63%, iwhich imeans ithe irole iof iPenjas iteachers iat iTanjung iBeringin iElementary iSchool iin iMusi iRawas iUtara iis iin ithe isufficient icategory. iMeanwhile, ithe iachievement ilevel iof ifacilities iand iinfrastructure ifor iPenjasorkes iat ithe ischool iis i65.61%.